The importance of preoperative T1 slope for determining proper postoperative C2–7 Cobb’s angle in patients undergoing cervical reconstruction - Jinshui Chen; Juying Wang; Xuepeng Wei; Huapeng Guan; Benhai Wang; Hao Xu; Jianmei Chen (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background This study aimed to explore the relationship among different cervical sagittal parameters in asymptomatic volunteers and the correlation between surgical efficacy and difference of presumed and actual postoperative C2–7 Cobbs’s angle (C2–7COBB), which was calculated based on preoperative T1 slope (T1S) in patients undergoing cervical reconstruction. Methods In total, 158 inpatients with cervical spondylosis and 274 asymptomatic volunteers were retrospectively reviewed. Cervical sagittal parameters, such as C2–7COBB, T1S, thoracic inlet angle (TIA), and neck tilt (NT), were compared. Then, the correlation among these parameters was analyzed in asymptomatic volunteers, and a regression equation between T1S and C2–7COBB was established and used to analyze the correlation among the Japanese Orthopaedic Association (JOA) score improvement, the sagittal parameters, and the difference between presumed and actual postoperative C2–7COBB in patients after cervical reconstruction. Results The mean T1S, C2–7COBB, and TIA were significantly decreased in patients (P < 0.01). T1S and NT had a strong correlation with TIA (P < 0.01). T1S demonstrated a moderate correlation with C2–7COBB in asymptomatic volunteers (r = 0.569, P < 0.01). A regression equation had been established as C2–7COBB = 0.742 × T1S − 0.866. The mean C2–7COBB and JOA score improved significantly (P < 0.05) postoperatively. Moreover, the JOA improvement rate showed a significant negative correlation with the difference in the presumed and actual postoperative C2–7COBB (r = − 0.696, P < 0.01). Conclusion Our study successfully established a regression equation for calculating postsurgical C2–7COBB based on the correlation between T1S and C2–7COBB in asymptomatic volunteers. The regression equation could be used for guiding surgeons to accomplish an ideal postsurgical C2–7COBB for patients with cervical spondylosis.